Do male athletes with already high initial haemoglobin mass benefit from 'live high–train low' altitude training?. Issue 1 (5th November 2017) - Hauser, Anna; Troesch, Severin; Steiner, Thomas; Brocherie, Franck; Girard, Olivier; Saugy, Jonas J.; Schmitt, Laurent; Millet, Grégoire P.; Wehrlin, Jon P.
Abstract : New Findings: What is the central question of this study? It has been assumed that athletes embarking on an 'live high–train low' (LHTL) camp with already high initial haemoglobin mass (Hbmass ) have a limited ability to increase their Hbmass further post‐intervention. Therefore, the relationship between initial Hbmass and post‐intervention increase was tested with duplicate Hbmass measures and comparable hypoxic doses in male athletes. What is the main finding and its importance? There were trivial to moderate inverse relationships between initial Hbmass and percentage Hbmass increase in endurance and team‐sport athletes after the LHTL camp, indicating that even athletes with higher initial Hbmass can reasonably expect Hbmass gains post‐LHTL. It has been proposed that athletes with high initial values of haemoglobin mass (Hbmass ) will have a smaller Hbmass increase in response to 'live high–train low' (LHTL) altitude training. To verify this assumption, the relationship between initial absolute and relative Hbmass values and their respective Hbmass increase following LHTL in male endurance and team‐sport athletes was investigated. Overall, 58 male athletes (35 well‐trained endurance athletes and 23 elite male field hockey players) undertook an LHTL training camp with similar hypoxic doses (200–230 h). The Hbmass was measured in duplicate pre‐ and post‐LHTL by the carbon monoxide rebreathing method. Although there was no relationship ( r  = 0.02, P  = 0.91) between initial absolute Hbmass (in grams) and the percentage increase in absolute Hbmass, a moderate relationship ( r  = −0.31, P  = 0.02) between initial relative Hbmass (in grams per kilogram) and the percentage increase in relative Hbmass was detected. Mean absolute and relative Hbmass increased to a similar extent ( P  ≥ 0.81) in endurance (from 916 ± 88 to 951 ± 96 g, +3.8%, P  < 0.001 and from 13.1 ± 1.2 to 13.6 ± 1.1 g kg −1, +4.1%, P  < 0.001, respectively) and team‐sport athletes (from 920 ± 120 to 957 ± 127 g, +4.0%, P  < 0.001 and from 11.9 ± 0.9 to 12.3 ± 0.9 g kg −1, +4.0%, P  < 0.001, respectively) after LHTL. The direct comparison study using individual data of male endurance and team‐sport athletes and strict methodological control (duplicate Hbmass measures and matched hypoxic dose) indicated that even athletes with higher initial Hbmass can reasonably expect Hbmass gain post‐LHTL. Abstract :